Quantitative Analysis of Eugenol in Different Parts of Clove - Khemariya, Prashant; Agrawal, Ankit; Kumar, Krishna; Tiwari, Aadrsh Kumar (The International Journal of Biotechnology, 2022)
Eugenol is the key active constituent of clove. The aim of this study was to analyze the concentration of Eugenol in different parts of dried Clove (tail, mid body and flower) by IR Spectroscopy and graphical comparison of the concentration. In this experiment the different part of dried clove was used to perform the quantitative analysis. Two methods were followed for the IR Spectroscopy, Attenuated Total Reflectance (ATR) sampling method and KBr Pellet method. KBr Pellets were prepared at 1:99 (Clove part: KBr) and IR spectrum drawn between IR reason (650 to 4000). Total 5 samples were analysed [Sample 01- Clove flower, Sample 02- just below of flower, Sample 03- mid body, Sample 4 -mid Body 2nd and Sample 05 -tail part]. Two wavelengths were target 1513 cm-1 and 1431 cm-1. The quantitative analysis was performed for % transmittance and % absorbance. Plotted Spectra was compared with the Spectral Database for Organic Compounds (SDOC) and spectra-base at Wiley. Sample 03 mid body shows higher area comparatively remaining four samples at both peaks (1513 cm-1 as well as 1431 cm-1). Results shows that the concentration of Eugenol is higher at Ovules than tail and flower.